Symbols in Chandra Shyam Dangol’s Stone Sculptures - Sharma, Yam Prasad (Madhyabindu Journal, 2022)
Chandra Shyam Dangol's stone sculptures have symbols that suggest the concepts of wisdom and enlightenment. The symbols are images that signify something else beyond themselves. The recurrent symbols in the sculptures are the figures of divinities, lotus, sword, mudras (gestures) of meditating characters and the image of Shivalinga. These mystical symbols suggest spiritual values. They make the viewers aware of the self and the external world and inspire the unity of these entities. Due to the mythical and spiritual subject matters, the works appear to be magical and mystical. The symbolic artworks enhance moral values and contribute to refine the civilization. 'Stone sculptures of Chandra Shyam Dangol', the area of this research, is explored from the symbolist perspective of Thomas Carlyle and Susanne K. Langer. Symbols suggest the silent aspects of reality. Symbols in Dangol's artworks suggest invisible spiritual dimensions of human experience. Since the paper derives the thesis statement through the interpretation of sculptures, and there are the possibilities of multiple interpretations, this research is qualitative.